Isolasi Katekin dari Gambir (Uncaria gambir (Hunter). Roxb) untuk Sediaan Farmasi dan Kosmetik - Rahmawati, Noveri; Bakhtiar, Amri; Putra, Deddi Prima (Jurnal Penelitian Farmasi Indonesia, 2013)
Study on isolation of catechin from gambier (Uncaria gambier (Hunter). Roxb) for pharmaceutical and cosmetic uses has been conducted.Raw materials of gambier were collected from three different areas including Andalas University Medicinal Plant Garden, Lima Puluh Kotaand Siguntur Pesisir Selatan, West Sumatera. Catechin was isolated from gambier using two methods, namely purification and pre nonpurification. Several evalutions on quality of the obtained catechin was done including descriptions of the catechins, solubility, colorreactions, thin layer chromatography, yield, drying shrinkage, melting point and maximum uptake levels of catechins. The best results forpharmaceutical and cosmetic uses are gambier originated from Siguntur with pre purification method which obtained 56.3% yield and 96.17%levels of catechins.